Mengukur Gerak-Laju Modernitas: Trayek Timur dan Barat WTBOS - Arsya, Deddy (Puitika, 2024)
The text discusses the trajectory of colonial modernity in two distinct "routes" connected to the Ombilin Coal Mining Heritage of Sawahlunto (WTBOS). Both routes entered the historical stage due to the discovery of abundant coal deposits. The focal point is Ombilin-Sawahlunto, a once uninhabited and secluded valley in the heart of Sumatra’s wilderness, but one rich with black-gold reserves. To transport this resource to global markets, the Dutch colonial government initially planned to use an eastern route but eventually chose and developed the western route. These choices led to vastly different fates for the two paths in terms of modernity. The eastern route, heading towards the Malacca Strait via Kuantan-Indragiri, was abandoned and thus remained largely untouched by significant elements of modernity. In contrast, the approved western route, which connected Sawahlunto to the West Coast of Sumatra, catalyzed rapid development in the regions it traversed, ushering them into the vibrant embrace of modernity. This dynamic transformation brought growth, progress, and stability, which remain strikingly evident even after more than 150 years.